Nulidades processuais - Sacilotto, Aline Karina Duarte (2019)
The system of procedural nullities, like the entire Brazilian procedural system, has undergone several doctrinal and jurisprudential discussions in recent years that have significantly reflected in the drafting of the New Code of Civil Procedure. With its consecration, there was a tendency to preserve to the maximum the procedural acts produced, applying several procedural principles such as the instrumentality of forms, sanity, among others, in the receipt of procedural acts, although imperfect, when they are able to achieve the purpose they intended. With this, the decree of nullity of acts became the last measure and only used when in fact there is no way to remedy the procedural act produced. For this verification, the doctrine created several subdivisions that allow us to better visualize each of these situations in the Brazilian procedural system. On the whole, most of the doctrine understood this new position as an overlapping of the attention of the parties to the exacerbated formalism that for many years governed proceduralist relations